Epidemiological analysis of influenza in Jiading District， Shanghai， 2013‒2023 - CHEN Wanqi; MA Feifei; WANG Guanghe; WANG Haoquan; DENG Senmiao; MAO Yuhua; SUN Pan; CHEN Weixin (Shanghai yufang yixue)
ObjectiveTo analyze the epidemiological characteristics and trends of influenza‑like illness (ILI) in Jiading District from 2013 to 2023, to explore the prevalence patterns, so as to provide a scientific basis for a better prevention and control of influenza.MethodsData of ILI cases, pathogenetic surveillance results and pathogen detection data from influenza surveillance network laboratories in Jiading District from 2013 to 2023 were collected for statistical analysis.ResultsFrom 2013 to 2023, the overall proportion of medical visits for ILI cases in Jiading District was 2.70%. ILI cases were mainly distributed in the age group of ≥25 years, with a seasonal prevalence characteristic, mainly concentrated in the winter and spring, with an occasional small peak in the summer. A total of 12 423 specimens were tested for pathogenetic surveillance and monitoring, 3 651 of which were tested positive for nucleic acid detection, with a positive rate of 29.39%. The dominant strain was influenza A (H3N2) virus, accounting for 55.05%. There were statistical significant differences in the positive detection rates by different streets and townships(χ2=24.73，P<0.05）. The influenza network laboratory isolated and cultured influenza viruses from 3 154 nucleic acid‑positive samples sent by national influenza sentinel surveillance hospitals using 2methodsMadin‑Darby canine kidney (MDCK) cells and specific pathogen free (SPF) chicken embryos, respectively, with a total isolation rate of 39.51%, and the isolation rate of MDCK cells (35.45%) was higher than that of SPF chicken embryos (5.36%). From 2013 to 2023, a total of 14 ILI outbreaks were reported in Jiading District, mainly in primary schools, kindergartens and secondary schools.ConclusionInfluenza in Jiading District, Shanghai, is mainly prevalent in the winter and spring, with different subtypes of influenza viruses alternating or co⁃circulating in different monitoring year. It is recommended to promote influenza vaccination, further improve influenza prevention and control measures, enhance health promotion to the age group of ≥25 years in winter and spring, and strengthen surveillance and monitoring on ILI outbreaks in collective units such as primary schools and childcare institutions, so as to reduce the disease burden.